AN INTRODUCTION TO THE ART OF ACCOUNTING. - Dohr, James L. (The Accounting Review, 1947)
Abstract The article presents an introduction to the art of accounting. The art of accounting has long been the subject matter of study by those who would become accounting technicians-controllers, auditors, public accountants, cost accountants and the like. For the purposes of this type of study, objectives have been formulated, teaching methods have been devised and a substantial body of text and other material has been developed. As a result the education of accounting technicians goes forward on a reasonably adequate basis although by no means without numerous possibilities of betterment. At the same time popular education in the art of accounting has been woefully neglected. For many of those who are not interested in becoming accounting technicians only inadequate inducement has been offered and only inadequate reasons have been given, for the study of accounting; for those who have evinced an interest in the art, despite their lack of desire to become technicians, the opportunities for study have, for the most part, been limited to the courses and procedures available for prospective technicians.